DNS analysis of turbulent vaporizing two-phase flows. Part II: Topology of the scalar field. (November 2022) - Onofre Ramos, Marcos Martín; Zhao, Song; Bouali, Zakaria; Mura, Arnaud
Abstract: This work is devoted to turbulence in two-phase flows with mass transfer, a fundamental research topic relevant to many applications including those related to two-phase flow combustion. The objective is to provide further insights into the influence of liquid/gas interfaces on some statistical characteristics of the fluctuating velocity and scalar fields collected in the gas phase. The second part of this study is focused on the analysis of the scalar field. The starting point is the transport equation for the mixture fraction. In most descriptions of two-phase flow combustion, the mixture fraction is indeed used to characterize the multicomponent mixture. However, considering the non-linear dependence of chemical reaction rates to composition, the single knowledge of its mean (or filtered) state is not sufficient to describe turbulent conditions. Its variance and mean (or filtered) scalar dissipation rate (SDR) must be evaluated, with the latter quantity (i.e., the SDR) driven, at leading order, by the velocity gradients relevant to straining effects and by the curvature of the mixture fraction field. In a first step of the present study, a detailed analysis of the (i) scalar field, (ii) its gradient, and (iii) the resulting dissipation rate is reported. It is subsequently completed by an exhaustive inspection of geometrical properties and alignment statistics. The corresponding statistical analysis makes use of conditional sampling based on a level-set which signs the distance to the interface, thus allowing to discriminate its influence on scalar and velocity gradients, as well as the resulting turbulence topology. Highlights: Direct Numerical Simulation (DNS) of turbulent two-phase flows are conducted. Scalar field topology is modified as the liquid/gas interface is approached. Log-normality of the SDR distribution is increased. Misalignment between the scalar gradient and vorticity is increased. Scalar mixing is enhanced in the vicinity of the liquid/gas interface.